Medicinal products, medical devices, or accessories of medical devices: How to qualify gases for spirometry? - Manellari, Sara; Leone, Maria Grazia; Casiraghi, Antonella; Gennari, Chiara Grazia Milena; Minghetti, Paola (Frontiers in Drug Safety and Regulation, 2022)
European legislation provides that each product used for healthcare purposes is regulated according to specific directives and regulations based on intended use and its mechanism of action. However, sometimes qualification issues may be aroused between medicinal products, medical devices and accessories of them. This is the case of gases for spirometry, which support spirometers in measuring the pulmonary capacity of patients. This article aims at discussing the criticisms connected to their proper regulatory qualification, detailing why they should more properly qualified as accessories of medical devices instead of medicinal products or medical devices.